Free Fatty Acids on the Integument of the Striped Flea Beetle, Phyllotreta striolata F., and Their Effects on Conidial Germination of the Entomopathogenic Fungi Metarhizium anisopliae, Beauveria bassiana and Paecilomyces fumosaroseus - T .P., Priyatno; Y. B., Ibrahim (Universiti Putra Malaysia Press, 2002)
Free fatty acids on the integument of the striped flea beetle, Phyllotreta striolata F., and their effects on the conidial germination of Metarhizium anisopliae (Metch.) Sorokin, Beauveria bassiana (Bals.) Vuill. and Paecilomyces fumosoroseus (Wise) Brown & Smith were investigated. Gas chromatographic analysis of adult flea beetle cuticular extracts showed two peaks exhibiting a retention time corresponding to those of butyric acid and nonanoic acid. Other fatty acids detected were caproic, heptanoic and caprylic acids. Toxicity of these fatty acids to conidial germinaton ofM. anisopliae, B. bassiana and P. fumosoroseus was dependent on their type and concentration. Butyric was the least toxic-{)nly toxic to B. bassiana and P. fumosoroseus at a concentration higher than 0.125%. However, at concentrations greater than 0.075 %, all of the fatty acids were very toxic. Nonanoic acid was the most toxic and it completely inhibited conidial germination at the lowest concentration of 0.025 %, especially to M. anisopliae and P. fumosoroseus. Heptanoic acid was very toxic to B. bassiana, allowing only 12.5% germination at the lowest concentration of 0.025%. It is surmised that straight-chain fatty acids on the flea beetle integument protected the beetles against the invasion of entomopathogenic fungi.